The Utilization of Digital Marketing, Product Quality, and Green Business Practices in Improving the Performance of Craft SMEs in Pasuruan City - Distyaning Tri Wahyuni; Antin Rakhmawati (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Improving the performance of craft small and medium-sized enterprises (SMEs) requires not only technology-enabled market expansion but also consistent product quality and environmentally responsible business practices. This study examined the associations between digital marketing utilization, product quality, green business practices, and the performance of craft SMEs in Pasuruan City. A quantitative explanatory design was employed. Data were collected using a Likert-scale questionnaire administered to 117 craft SME owners selected through purposive sampling and analyzed using multiple linear regression. The results indicated that digital marketing utilization was not significantly associated with SME performance, whereas product quality and green business practices showed positive and significant associations. Green business practices emerged as the strongest predictor of performance. Collectively, the three variables were significantly associated with SME performance and explained 71.9% of its variance. These findings indicate that adopting digital marketing alone may be insufficient to improve business performance unless it is supported by high-quality products and environmentally sustainable practices. The study contributes empirical evidence that craft SME development should prioritize an integrated strategy that strengthens product quality and green business practices while transforming digital marketing from a basic promotional instrument into a strategic organizational capability.